Laterality of auditory startle responses in humans - Kofler, Markus; Müller, Jörg; Rinnerthaler-Weichbold, Martina; Valls-Solé, Josep (Clinical neurophysiology, 2008)
To examine whether the auditory startle reaction in humans is a symmetrical or asymmetrical bilateral brainstem reflex in response to an unexpected loud stimulus. We investigated physiological side-to-side differences of auditory startle responses (ASRs) in 28 healthy adult subjects. ASRs were elicited by randomly presented auditory stimuli. Reflex electromyographic activity was simultaneously recorded from masseter, orbicularis oculi, sternocleidomastoid and biceps brachii muscles bilaterally. ASR area-under-the-curve was significantly larger on the side contralateral to hand dominance in sternocleidomastoid, and tended to be larger on the dominant side in biceps brachii. In contrast, in orbicularis oculi, ASR area was significantly larger on the right vs. left side, irrespective of handedness. There was no significant side-to-side difference of ASR probability and ASR latency in any muscle. The present data expand our knowledge on physiological variables influencing ASRs and provide evidence of laterality of ASRs in sternocleidomastoid and biceps brachii, being associated with hand dominance, and in orbicularis oculi, irrespective of handedness. Normal limits of side-to-side differences offer an additional parameter to be taken into account in studies of patients presenting with asymmetric symptoms.